(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract: In recent years, pedagogical approaches have changed radically in the processes of language learning. Globally, the communicative approach to learning and teaching English has become popular as an advanced methodological direction. Among modern language learning methods, CLT, or Communicative Language Teaching, has been recognized as one of the most effective approaches to foreign language acquisition worldwide. This method has taken foreign language learning to a new level in terms of quality and efficiency, using neuro-linguistic and cognitive psychology, language and speech theory, and modern interactive technologies.